1994
DOI: 10.3758/bf03206954
|View full text |Cite
|
Sign up to set email alerts
|

The gender-marking effect in spoken word recognition

Abstract: In this paper we examine whether the recognition of a spoken noun is affected by the gender marking-masculine or feminine-that is carried by a preceding word. In the first of two experiments, the gating paradigm was used to study the access of French nouns that were preceded by an appropriate gender marking, carried by an article, or preceded by no gender marking. In the second experiment, subjects were asked to make a lexical decision on the same material. A very strong facilitatory effect was found in both c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
63
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(65 citation statements)
references
References 17 publications
1
63
1
Order By: Relevance
“…This includes effects of gender priming on lexical decision and gating in French (Grosjean, Dommergues, Cornu, Guillelmon, & Besson, 1994), on word repetition and gender classi-fication in Italian , and on picture naming in Spanish (Reyes, 1995) and German (Hillert & Bates, 1996; but see van Berkum, 1996, andFriederici &Schriefers (1994) for reports indicating that gender priming may be relatively fragile in German and Dutch). Studies of lexical decision in Serbo-Croatian provide evidence for both gender and case priming, with real-word and nonword primes that carry morphological markings that are either congruent or incongruent with the target word (Gurjanov, Lukatela, Moskovljevic, & Turvey, 1985;Lukatela, Kostic, Feldman, & Turvey, 1983).…”
Section: On the Inseparability Of Grammar And The Lexicon In Normmentioning
confidence: 99%
“…This includes effects of gender priming on lexical decision and gating in French (Grosjean, Dommergues, Cornu, Guillelmon, & Besson, 1994), on word repetition and gender classi-fication in Italian , and on picture naming in Spanish (Reyes, 1995) and German (Hillert & Bates, 1996; but see van Berkum, 1996, andFriederici &Schriefers (1994) for reports indicating that gender priming may be relatively fragile in German and Dutch). Studies of lexical decision in Serbo-Croatian provide evidence for both gender and case priming, with real-word and nonword primes that carry morphological markings that are either congruent or incongruent with the target word (Gurjanov, Lukatela, Moskovljevic, & Turvey, 1985;Lukatela, Kostic, Feldman, & Turvey, 1983).…”
Section: On the Inseparability Of Grammar And The Lexicon In Normmentioning
confidence: 99%
“…However, several studies have also reported facilitative priming effects of gender. For example, gender facilitation was observed for word pairs in French using gating and auditory lexical decision (Grosjean et al, 1994) and in Italian and Russian (Akhutina et al, 1999) using cued shadowing. In these studies, the gender of a word facilitated its retrieval relative to words that provided no gender information.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have used the gender of nouns to investigate word retrieval and word production (e.g., Akhutina, Kurgansky, Polinsky, & Bates, 1999;Bates, Devescovi, Hernandez, & Pizzamiglio, 1996;Bates, Devescovi, Pizzamiglio, Damico, & Hernandez, 1995;Bentrovato, Devescovi, D'Amico, & Bates, 1999;Bentrovato, Devescovi, D'Amico, Wicha, & Bates, 2003;Grosjean, Dommergues, Cornu, & Guillelmon, 1994;Jacobsen, 1999;van Berkum, 1997;Vigliocco & Franck, 1999;Vigliocco, Lauer, Damian, & Levelt, 2002;Vigliocco, Vinson, Indefrey, Levelt, & Hellwig, 2004;Vigliocco & Zilli, 1999), cohort activation in word recognition (e.g., Dahan, Swingley, Tanenhaus, & Magnuson, 2000), processing differences between pictures and words (e.g., Bowers, Vigliocco, Stadthagen-Gonzalez, & Vinson, 1999), the relative timing of syntactic and phonological processes during lexical access (e.g., Schmitt, Rodriguez-Fornells, Kutas, & Munte, 2001a;Schmitt, Schiltz, Zaake, Kutas, & Munte, 2001b;van Turennout, Hagoort, & Brown, 1998) and the interplay between discourse, semantic, and syntactic level processes (e.g., Brown, van Berkum, & Hagoort, 2000;Deutsch & Bentin, 2001;Deutsch, Bentin, & Katz, 1999;Gunter, Friederici, & Schriefers, 2000;Gunter, Stowe, & Mulder, 1997;Hagoort, 2003;van Berkum, Brown, & Hagoort, 1999;Wicha, 2002;Wicha, Bates, Moreno, & Kutas, 2000). Recent studies have also provided electrophysiological evidence for the brain's sensitivity to gender agreement during sentence comprehension (e.g., Brown et al, 2000;Demestre, Meltzer, Garcia-Albea, & Vigil, 1999;Deutsch & Bentin, 2001;…”
Section: Introductionmentioning
confidence: 99%
“…And, indeed, empirical results from a variety of tasks suggest a number of ways in which gender information might facilitate decisions about, or processing of, pictures and words. Gender markings on a noun have been shown to expedite its recognition (Grosjean et al, 1994;Bates et al, 1995;Radeau and van Berkum, 1996). Lexical decisions for nouns are speeded by the prior occurrence of an article or adjective that agrees with it in gender (Gurjanov, 1985;Lukatela et al, 1987;Jakubowicz and Faussart, 1998).…”
Section: Introductionmentioning
confidence: 99%